Organizational Management Training at the Student Association (HMPS) at UNIDA Gontor - Wicaksana, Febrian Arif; Ardiani, Yana Elita; Sa'adah, Yaumi; Rachmawati, Andini; Cahyani, Meitria (Society : Jurnal Pengabdian Masyarakat, 2025)
Improving the quality of human resources in an organization is divided into two aspects, the first is the physical aspect, and the second is the non-physical aspect. The Prodi Student Association (HMP) organization is a study program student organization at Darussalam Gontor University. This student organization, which is in the realm of study programs under the faculty and senate, is a forum for students to improve reasoning, interests and talents, and student welfare in student life in higher education. This student organization is organized from, by, and for students under the guidance of study programs at Darussalam Gontor University. With this student organization, they are expected to have soft skills. HMP itself was formed to prepare students to have organizational skills, develop their interests and talents, become good leaders. And have adequate managerial skills.  Organizational training is held as an effort to equip organization members with the knowledge and skills needed to carry out their duties and responsibilities.